Implementation of Clinical Practice Guidelines in the Health Care Setting: A Concept Analysis. (October 2019) - Beauchemin, Melissa; Cohn, Elizabeth; Shelton, Rachel C.
Abstract : The literature is replete with clinical practice guidelines (CPGs) and evidence supporting them. Translating guidelines into practice, however, is often challenging. We conducted a concept analysis to define the concept of "implementation of CPGs in health care settings." We utilized Walker and Avant's methodology to define the concept of "implementation of CPGs in health care settings." This included a focused review of the literature, defining the relevant attributes, defining implementation, case examples, and antecedents and potential consequences from implementation of CPGs in health care settings. The concept "implementation" is complex, with numerous frameworks, facilitators, and barriers to implementation described in the literature. The existing literature supports our definition of implementation of CPGs in a health care setting as a process of changing practice in health care while utilizing the best level of evidence that is available in the published literature. These include 7 attributes necessary for effective implementation. Implementation of CPGs in health care settings requires an ongoing iterative process that considers these attributes and is inclusive to administrators, clinicians, and patients to ensure guidelines are understood, accepted, implemented, and evaluated for continued adoption of best practices. Ongoing efforts inclusive at all steps of implementation across multiple levels are needed to effectively change practice.